Peran Makromineral pada Reproduksi Ruminansia - Yanuartono Yanuartono; Soedarmanto Indarjulianto; Alfarisa Nururrozi; Hary Purnamaningsih (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
Macromineral is one component of a nutrient that has an important role in the growth, health, production,reproduction and immune system of animals. Ruminants need makromineral such as Ca, P, Mg, K, Na , Cl and S. Mineral needs of ruminant affected by several factors such as their age, pregnancy and lactation status.Mineral deficiency can cause disturbances in reproduction ruminant. Ca and P have direct influence while Mg, K, Na, Cl and S acted indirectly on reproductive function. A complete understanding of the role macromineral on ruminant reproductive function is indispensable for the prevention of their reproductive disorders due toimproper feeding minerals.